Desentralisasi Pelayanan Publik Melalui Representasi UPTD Dukcapil untuk Meningkatkan Aksesibilitas di Wilayah Terpencil - Muhammad Helvanza; Suci Prasita Dewi (Institut Pemerintahan Dalam Negeri, 2025)
This study analyzes the implementation of public service decentralization through the representation of the Population and Civil Registration Technical Implementation Unit (UPTD Dukcapil) in improving the accessibility of civil registration services in remote areas. Using a qualitative case study approach at the UPTD Dukcapil of Merlung Subdistrict, Tanjung Jabung Barat Regency, data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman interactive model. The findings show that the reactivation of the UPTD after the deactivation of the Machine to Machine (M2M) network significantly increased public access to civil registration services, recording 133 services in three operational days, dominated by e-ID card (e-KTP) registrations. Merlung’s strategic location positions it as a service hub for surrounding and neighboring districts. However, challenges persist, including logistical shortages, power outages, and limited local authority due to the unit’s subordination to the regency’s civil registration office. The study concludes that decentralization through UPTD effectively reduces spatial barriers and service disparities but requires stronger resource support, institutional coordination, and a balanced policy between national standardization and local responsiveness.